(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2008)
This research aims to improve the process Tax accounting by using the scientific method to such as Six Sigma DMAIC steps called in General. Authority for Tax accounting . this approach has been described Tax accounting process Fully and identify problems experienced by the measurement and analysis and identify the critical success factors to satisfy customers and adoption process redesign Tax accounting process with the possibility of obtaining a high-quality revenue to be used by the body to improve its performance . Collected data and information from interviews with officials, staff and see the details & the conduct & operations in the body, and used well as a questionnair to measure the quality & services present action by the body, Been using traditional and modern tools for the analysis & data and information collected for the purpose & evaluating performance and determining factors and causes chain person and subsidiary affecting the function of power of tax. Particular results & the study showed application & comprehensive quality management system tools , as ( Six Sigma ) system and that the process & not based on fats mutual trust between the holders and power & tax, the low level of services delivery led to five gaps in performance & the body , weak tax revenues and unstable , the tax accounting system suffers from comprehensive and interrelated problems related to domestic environment , the training component is of primary importance in improving accounting process , Justice is the first priority in obtaining high-quality system of income, Financial statements , submitted to the body beyond the limits & statistical control after evidence physical a few influential in the critical success factors . The researcher with practical system is built Six sigma basis for improved performance as well as future research topics in this the research conclude the necessity body to start treating all main & subsidiary casa on power tax functioning as well as necessity implantation which stated by house of quality and try executes all them .